2020
DOI: 10.3390/ijms21239310
|View full text |Cite
|
Sign up to set email alerts
|

The Role of β-Arrestins in Regulating Stem Cell Phenotypes in Normal and Tumorigenic Cells

Abstract: β-Arrestins (ARRBs) are ubiquitously expressed scaffold proteins that mediate inactivation of G-protein-coupled receptor signaling, and in certain circumstances, G-protein independent pathways. Intriguingly, the two known ARRBs, β-arrestin1 (ARRB1) and β-Arrestin2 (ARRB2), seem to have opposing functions in regulating signaling cascades in several models in health and disease. Recent evidence suggests that ARRBs are implicated in regulating stem cell maintenance; however, their role, although crucial, is compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 82 publications
(126 reference statements)
0
11
0
Order By: Relevance
“…Indeed, some of the abnormal AS events were associated with drug sensitivity and resistance of NSCLC (Motegi et al, 2019;Pilié et al, 2019) as well as cell adhesion molecule binding process (Song et al, 2013;Hintermann and Christen, 2019). Our KEGG analysis showed that the genes in the m6A-related AS events significantly participated in the GPCR signaling in LUAD, and the latter is mediated by three major G protein subclasses and each subclass also has multiple proteins that are products due to the AS events (Kang et al, 2015;Kallifatidis et al, 2020). Similarly, we found the m6A-related AS events in the TGF-β signaling in LUSC.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, some of the abnormal AS events were associated with drug sensitivity and resistance of NSCLC (Motegi et al, 2019;Pilié et al, 2019) as well as cell adhesion molecule binding process (Song et al, 2013;Hintermann and Christen, 2019). Our KEGG analysis showed that the genes in the m6A-related AS events significantly participated in the GPCR signaling in LUAD, and the latter is mediated by three major G protein subclasses and each subclass also has multiple proteins that are products due to the AS events (Kang et al, 2015;Kallifatidis et al, 2020). Similarly, we found the m6A-related AS events in the TGF-β signaling in LUSC.…”
Section: Discussionmentioning
confidence: 84%
“…Among the increased proteins following RBPMS knockdown, the two ARRB members—ARRB1 and ARRB2—are deregulated in many cancer types and have been linked to the inhibition of the senescence and growth as well as the promotion of the self-renewal, progression, and invasion of cancerous cells [ 39 , 40 , 81 ]. Moreover, CPT1A plays a crucial role in radioresistant and chemoresistant phenotypes in diverse cancer types [ 41 , 42 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…ARRB1 also enhances endothelial cell proliferation and tube formation triggered by VEGF-C [9] .ARRB1 has been demonstrated to be important in the control of stem cell characteristics, with a role in both normal and malignant stem cells [14] . ARRB stimulates the proliferation of embryonic stem cells, and in the dentate gyrus (DG) of the adult hippocampus, ARRB1 also regulates BMP2 transcription to regulate the proliferation of neural precursors.…”
Section: Discussionmentioning
confidence: 99%